A Novel Tomato Fusarium Wilt Tolerance Gene - Prihatna, Cahya; Barbetti, Martin J.; Barker, Susan J. (Frontiers in Microbiology, 2018)
The reduced mycorrhizal colonization (rmc) tomato mutant is unable to form mycorrhiza and is more susceptible to Fusarium wilt compared with its wild-type isogenic line 76R. The rmc mutant has a chromosomal deletion affecting five genes, one of which is similar to CYCLOPS. Loss of this gene is responsible for non-mycorrhizality in rmc but not enhanced Fusarium wilt susceptibility. Here we describe assessment of a second gene in the rmc deletion, designated Solyc08g075770 that is expressed in roots. Sequence analyses show that Solyc08g075770 encodes a small transmembrane protein with putative phosphorylation and glycosylation sites. It is predicted to be localized in the plasma membrane and may function in transmembrane ion transport and/or as a cell surface receptor. Complementation and knock-out strategies were used to test its function. Some putative CRISPR/Cas-9 knock-out transgenic events exhibited Fusarium wilt susceptibility like rmc and some putative complementation lines were 76R-like, suggesting that the tomato Solyc08g075770 functions in Fusarium wilt tolerance. This is the first study to demonstrate that Solyc08g075770 is the contributor to the Tfw locus, conferring tolerance to Fol race 3 in 76R which was lost in rmc.